ENGLISH TEACHER IDENTITY CONSTRUCTION: INDONESIAN TEACHERS’ MOTIVATION AND STRATEGIES IN TEACHING ENGLISH FOR SPECIAL NEEDS STUDENTS - Yunika Upa; Concilianus Laos Mbato (PROJECT (Professional Journal of English Education), 2020)
Being a teacher in special needs school is not an easy job. Besides having to possess knowledge about children with special needs, special needs school teachers are required to have high patience and good mentality at work. One factor that affects the teachers’ success in educating students at special needs school, is the teachers’ motivation in carrying out their obligation. This study aimed to investigate what factors affected Indonesian teachers’ motivation in shaping and developing their identities and what strategies they used in teaching students with special needs.Using a qualitative method, the researchers gained data by interviewing teachers from two special needs schools in Yogyakarta, Indonesia. After analyzing the data, the researchers found that both intrinsic factors such as the desire to assist students with special needs to be more independent, and extrinsic factors such as family, students, and colleagues influenced the teachers’ motivation to teach in special needs schools in Yogyakarta. These factors played an important role in developing and shaping the teachers’ identity. The researchers also found that audio visual materials became the most effective and helpful strategies in teaching English for special needs schools. This study offers some suggestions for future researchers and Indonesian government.Keywords: Teacher Identity, motivation, teaching strategies, audio visual materials